Creating an effective asset integrity program. Issue 2 (20th October 2018) - Moyer, Lauren; Hedlund, Matthew
Abstract : Establishing an effective asset integrity management (AIM) program begins with the creation of a leadership team at the appropriate level of management. The team membership should encompass all areas of responsibility for asset integrity. Management at the corporate level cannot effectively drive execution of the details. Oversight at a low level in the organization can result in inconsistencies in implementation across the enterprise or insufficient resources to fully implement the AIM program. The AIM program should drive overall risk management for all assets. Regulatory covered processes may have higher safety risks, but non‐covered assets may still pose significant business risk that requires elevated coverage. The AIM program should be established as a full life cycle program, from design to decommissioning. Clearly defining and documenting standards, roles, and responsibilities for each phase of the life cycle are essential to an effective AIM program. Each role needs to be filled with subject‐matter experts who are actively engaged with the leadership team. A successful AIM program can improve existing risk management and reliability efforts through appropriate management direction, thoughtful application of the program to all assets, and clear documentation of the expectations for the full life cycle of the equipment. © 2018 American Institute of Chemical Engineers Process Saf Prog 38: e12008, 2019